Предмет: Химия,
автор: NikitaB1290
K2CO3 + HCl
Na2S+H2SO4
K2SiO3+HNO3
Полное ионное и сокращенное
Ответы
Автор ответа:
0
1) K2CO3 + 2HCl -> 2KCl + H2O + CO2
2K[+] + CO3[2-] + 2H[+] + 2C[-] -> 2K[+] + 2Cl[-] + H2O + CO2
CO3[2-] + 2H[+] -> CO2 + H2O
2) Na2S + H2SO4 -> Na2SO4 + H2S
2Na[+] + S[2-] + 2H[+] + SO4[2-] -> 2Na[+] + SO4[2-] + H2S
2H[+] + S[2-] -> H2S
3) K2SiO3 + 2HNO3 -> H2SiO3 + 2KNO3
2K[+] + SiO3[2-] + 2H[+] + 2NO3[-] -> H2SiO3 + 2K[+] + 2NO3[-]
2H[+] + SiO3[2-] -> H2SiO3
Прошу вас.
2K[+] + CO3[2-] + 2H[+] + 2C[-] -> 2K[+] + 2Cl[-] + H2O + CO2
CO3[2-] + 2H[+] -> CO2 + H2O
2) Na2S + H2SO4 -> Na2SO4 + H2S
2Na[+] + S[2-] + 2H[+] + SO4[2-] -> 2Na[+] + SO4[2-] + H2S
2H[+] + S[2-] -> H2S
3) K2SiO3 + 2HNO3 -> H2SiO3 + 2KNO3
2K[+] + SiO3[2-] + 2H[+] + 2NO3[-] -> H2SiO3 + 2K[+] + 2NO3[-]
2H[+] + SiO3[2-] -> H2SiO3
Прошу вас.
Автор ответа:
0
K2CO3 + 2HCl = 2KCl + CO2 + H2O
2K(+) + CO3(2-) + 2H(+) + 2Cl(-) = 2K(+) + 2Cl(-) + CO2 + H2O
CO3(2-) + 2H(+) = CO2 + H2O
Na2S + H2SO4 = Na2SO4 + H2S
2Na(+) + S(2-) + 2H(+) + SO4(2-) = 2Na(+)+ SO4(2-) + H2S
S(2-) + 2H(+) = H2S
K2SiO3 + 2HNO3 = 2KNO3 + H2SiO3
2K(+) + SiO3(2-) + 2H(+) + 2NO3(-) = 2K(+) + 2NO3(-) + H2SiO3
SiO3(2-) + 2H(+) = H2SiO3
2K(+) + CO3(2-) + 2H(+) + 2Cl(-) = 2K(+) + 2Cl(-) + CO2 + H2O
CO3(2-) + 2H(+) = CO2 + H2O
Na2S + H2SO4 = Na2SO4 + H2S
2Na(+) + S(2-) + 2H(+) + SO4(2-) = 2Na(+)+ SO4(2-) + H2S
S(2-) + 2H(+) = H2S
K2SiO3 + 2HNO3 = 2KNO3 + H2SiO3
2K(+) + SiO3(2-) + 2H(+) + 2NO3(-) = 2K(+) + 2NO3(-) + H2SiO3
SiO3(2-) + 2H(+) = H2SiO3
Похожие вопросы
Предмет: Алгебра,
автор: danil274730
Предмет: Математика,
автор: zritelanime
Предмет: Математика,
автор: gabdullinanoni
Предмет: История,
автор: Vanesso4ka